Impacts of compound precipitation extremes on belowground dynamics in a mesic grassland - Slette, Ingrid Jane, author; Knapp, Alan, advisor; Smith, Melinda, committee member; Iversen, Colleen, committee member; Conant, Rich, committee member (Colorado State University. Libraries, 2021)
Climate change is altering precipitation regimes globally and is expected to cause more frequent and extreme droughts as well as intensification of precipitation patterns (e.g., fewer and larger precipitation events) in many regions around the world. Drought has long been a phenomenon of interest to ecologists and has been widely studied as a key driver of ecosystem dynamics. To study drought, ecologists must define or at least operationalize what constitutes drought conditions. How this is accomplished in practice is unclear, so I begin my dissertation with a literature review that assessed how ecologists describe and study drought. I found that few publications explicitly define drought and that many (~30%) provide little quantification of studied droughts at all, simply equating drought with generally dry conditions. This lack of description hampers synthesis and our ability to draw broad ecological conclusions about drought impacts. I suggest that future publications provide detailed descriptions of drought conditions and contextualization within site-specific long-term climatic history, to facilitate more rigorous comparisons among studies. Our understanding of the ecological impacts of drought is further limited by the fact that most previous research has focused on the impacts of single drought events, and it is increasingly likely that droughts will be compounded with other precipitation changes (e.g., intensified precipitation patterns or previous droughts). To study how the impacts of drought are altered when compounded with other precipitation changes, I imposed a 2-yr extreme drought (growing season precipitation reduced 66%) in two different long-term precipitation experiments at the Konza Prairie Biological Station- one which had intensified precipitation patterns by imposing a treatment of fewer and larger precipitation events with longer intervening dry periods for 16 years (chapter 2), and one which had imposed a previous extreme drought (chapter 3). I found that though precipitation pattern intensification reduced aboveground net primary production (ANPP), it did not alter the response of ANPP to a subsequently imposed drought. In contrast, previous exposure to intensified precipitation patterns reduced belowground net primary production (BNPP) and muted soil CO2 flux responses to rainfall events during drought. In the case of multiple droughts, I found that repeated drought decreased root mass production more than twice as much as one drought (-63% vs. -27%, respectively, relative to controls). Thus, in both experiments, previous exposure to precipitation change decreased the resistance of BNPP to a subsequent drought. These results suggest that drought impacts might be underestimated if precipitation history and/or belowground impacts are not fully considered. Overall, my dissertation results indicate that understanding and prediction of ecological drought effects can be improved with more detailed and consistent descriptions of drought conditions and greater consideration of past precipitation changes and belowground dynamics.
Keywords: drought; climate change; precipitation regimes; precipitation history; belowground impacts